Grid-tied Converter with Intermediate Storage Chain for Multipurpose Applications - Ramonas, C.; Adomavicius, V. (Elektronika ir Elektrotechnika, 2011)
Rapidly developing renewable power systems enhanced role of the power electronics in sector of power engineering and raisedaccelerated development of power electronics’ industry. Results of research presented in this paper are related with small-scale hybridsolar-wind power system. The system has innovative grid-connected converter for multipurpose applications. The main peculiarity ofthe conversion system is the intermediate power storage chain (DC/DC converter) integrated with the grid inverter. Research of thehybrid system operation was carried out by means of the mathematical simulation. The researches disclosed that variations of solarirradiance and wind speed have significant impact to operation of the researched hybrid power plant, especially to the inverter’s reactivepower. Preliminary researches also confirmed possibility of the inverter’s reactive power control by adjusting phase of the modulationvoltage in respect of grid voltage. Wind and solar subsystems of the researched hybrid power system were found not having harmfulimpact to each other. Ill. 12, bibl. 8 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.113.7.605